PENGARUH RETURN ON ASSET, EARNING PER SHARE, DAN CURRENT RATIO TERHADAP HARGA SAHAM - Dammyanti, Sintia; Tjakrawala, F.X. Kurniawan (Jurnal Paradigma Akuntansi, 2024)
This research aims to determine and analyze the effect of return in assets, earnings per share and current ratio on stock prices in manufacturing industries that have been listed on the Indonesia Stock Exchange in the period 2015 to 2019. The sample was selected by purposive sampling method after being calculated by the slofin method. The data that has been obtained by researchers and valid to be studied are 40 companies. The researcher uses data processing techniques using regression analysis assisted by the IBM SPSS version 23 program. The results obtained by this study indicate that return on assets and earnings per share have a significant effect on stock prices and the current ratio has no significant effect on stock prices. However, when it is examined again that return on assets, earnings per share and current ratio have a positive influence on stock prices. This makes investors look more at the return on assets and earnings per share which can increase stock prices than the current ratio. For further research, moderating variables can be added so that the results will be more varied than others.